Headache disorders in patients with Ehlers-Danlos syndromes and hypermobility spectrum disorders - Mehta, Dwij; Simmonds, Lucy; Hakim, Alan J; Matharu, Manjit (Frontiers in Neurology, 2024)
Extra-articular symptoms, including headaches, are frequently encountered in patients with Ehlers-Danlos syndrome (EDS) and hypermobility spectrum disorders (HSD), and may be the presenting complaint. Migraine is reported in up to three quarters of patients with symptomatic joint hypermobility, have a higher headache frequency, and an earlier age of onset compared to the general population. Orthostatic headache is an important presentation, and should raise suspicion of an underlying spinal cerebrospinal fluid leak, dysautonomia, and craniocervical pathology, which are all associated with heritable connective tissue disorders (HCTD) including EDS. Any proposed invasive procedure should be scrupulously balanced against its potential risks, taking into account the type of EDS (e.g., vascular EDS) and its systemic manifestations. This is particularly pertinent when suspecting craniocervical instability since it remains a controversial diagnosis with a limited treatment evidence-base. This article reviews the commonly encountered headache disorders in patients with joint hypermobility-related conditions with a focus on EDS and HSD, describes their diverse presentations, and an overview of the recommended management strategies. It also emphasises the need for increased awareness of comorbid conditions in EDS and HSD among clinicians treating headaches to ensure a patient-tailored approach and facilitate a multidisciplinary approach in managing often complex cases.